Does Agricultural Support Policy Affect Crop Production in Turkey? - Canbay, Şerif (Bartın Üniversitesi, 2021)
One of the most basic requirements of humanity is the need for nutrition. Therefore, the demand for food products that do not have a substitute for human life is quite heavy. To this end, the agricultural sector becomes prominent to meet the need for nutrition but puts economic units in a great search. In this context, the agricultural sector is an important dynamic of the country's economies. This study seeks to answer how support and incentives for the agricultural sector affect agricultural crop production. In this context, the ARDL bounds test with a structural break was conducted using Turkey's 1995-2018 data to determine the effects of agricultural supports on agricultural crop production. According to the analysis results, it was found out that agricultural supports in Turkey positively affect agricultural crop production in both the short and long term.
Keywords: Economics; Ekonomi